Myofibroblasts in Normal and Fibrotic Liver in Different Animal Species - Vladimir Kukolj (Sciendo, 2014)
Myofibroblasts, cells sharing characteristics with fibroblasts and smooth muscle cells, may have a very heterogeneous origin. The myofibroblasts may be derived from a variety of sources including resident mesenchymal cells, epithelial to mesenchymal transition, as well as from circulating fibroblast-like cells called fibrocytes that are derived from bone-marrow stem cells, or derived from bone marrow precursors. In normal conditions, fibroblastic cells exhibit a low extracellular matrix production ability. After tissue injury, they become activated by cytokines locally released from inflammatory and resident cells to migrate into the damaged tissue and to synthesize extracellular matrix components. The investigation of cytoskeletal and cell surface markers showed a certain degree of heterogeneity of these cells. The reason for this is that markers these cells express to a large extent depend on the type of animal, age and stage of development of fibrosis. A better knowledge of the molecular mechanisms involved in the appearance of differentiated myofibroblasts in different pathological situations will be useful for understanding the development of fibrosis, its prevention and therapy